2016
DOI: 10.1051/matecconf/20166600007
|View full text |Cite
|
Sign up to set email alerts
|

Interval of Routine Maintenance and Maintenance Performance: A Literature Review

Abstract: Abstract. In high-rise residential buildings, the quality of facilities management services is significant to the normal operation of the facilities. Unfortunately, lack of concern towards building maintenance, especially preventive maintenance, happens in domestic housing industry in Malaysia. Majority of the maintenance operations of condominiums suffer from lack of planning, lack of proactive maintenance plan, and lack of proper implementation. Thus, this paper reviews the implementation of preventive maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Works with analogous points or features identified – Yin Lee and Scott (2009), Straub (2012), Falorca et al (2013a), Lateef Olanrewaju and Abdul-Aziz (2015) and Mydin (2017). A bibliometric study, with the aim of creating the basis of a catalogue of bibliographic resources, to be used in conjunction with the SIAPME future computerised platform and to be made available to SIAPME users and managers. Studies can be found, some reflecting upon bibliometric analysis (Falorca et al , 2014; Santos et al , 2017), literature searches (Wing et al , 2016) and literature analysis and reviews (Au-Yong et al , 2016; Che-Ghani et al , 2016; Puķīte and Geipele, 2017; Lohmann et al , 2017; Galán and Gómez, 2018; Chong et al , 2018). An insight into cases of models and systems for MM, with origin, development and application in the field of industrial maintenance, as this can be a source area for such theory and operability of the BM.…”
Section: Methodological Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Works with analogous points or features identified – Yin Lee and Scott (2009), Straub (2012), Falorca et al (2013a), Lateef Olanrewaju and Abdul-Aziz (2015) and Mydin (2017). A bibliometric study, with the aim of creating the basis of a catalogue of bibliographic resources, to be used in conjunction with the SIAPME future computerised platform and to be made available to SIAPME users and managers. Studies can be found, some reflecting upon bibliometric analysis (Falorca et al , 2014; Santos et al , 2017), literature searches (Wing et al , 2016) and literature analysis and reviews (Au-Yong et al , 2016; Che-Ghani et al , 2016; Puķīte and Geipele, 2017; Lohmann et al , 2017; Galán and Gómez, 2018; Chong et al , 2018). An insight into cases of models and systems for MM, with origin, development and application in the field of industrial maintenance, as this can be a source area for such theory and operability of the BM.…”
Section: Methodological Approachmentioning
confidence: 99%
“…A bibliometric study, with the aim of creating the basis of a catalogue of bibliographic resources, to be used in conjunction with the SIAPME future computerised platform and to be made available to SIAPME users and managers. Studies can be found, some reflecting upon bibliometric analysis (Falorca et al , 2014; Santos et al , 2017), literature searches (Wing et al , 2016) and literature analysis and reviews (Au-Yong et al , 2016; Che-Ghani et al , 2016; Puķīte and Geipele, 2017; Lohmann et al , 2017; Galán and Gómez, 2018; Chong et al , 2018).…”
Section: Methodological Approachmentioning
confidence: 99%
“…Since this paper aimed to review the implementation of preventive maintenance and importance of routine maintenance for the building facilities and services in high-rise residential buildings, an extensive examination and evaluation of the relevant research works were conducted. This method referred to the studies completed by Simoes et al (2011), Roda et al (2014 and Au-Yong et al (2016). The literature search and evaluation encompassed published documents like articles in the journal, conference papers and books.…”
Section: Methodsmentioning
confidence: 99%
“…This situation may cause the inspection and repair procedure to be delayed. The inspection and maintenance schedule is likely to impact the maintenance performance and the satisfaction of the residents’ (Au-Yong et al , 2016).…”
Section: Efficient Operation and Maintenance Frameworkmentioning
confidence: 99%